The effectiveness of dental and oral health education for youth through online media - Haria FITRI; Filzdah Nurul FAJRIN; Nila KASUMA; Reno Wiska WULANDARI; Suci Rahma SARI; Giant ERNESTO (Journal of Syiah Kuala Dentistry Society, 2022)
Dental and oral health is essential for human life and is part of general health. However, many still donot know that the oral cavity plays a critical role in health. The COVID-19 pandemic has hampered teaching andlearning in class, but this can be solved virtually through online media. This study aims to determine youth'sknowledge about dental and oral health problems. The research is a cross-sectional analytic study conducted on 57students of X1 IPA class - SMA Pembangunan Laboratorium UNP - Padang, which met the inclusion and exclusioncriteria. A purposive sampling technique was used to select respondents. The educational process was donevirtually with an online meeting application. The activity stages consist of answering the pre-test, the educationalprocess, and answering the post-test. Students' background knowledge was measured using a questionnaireconsisting of 10 closed questions, giving one score when the answer was correct and 0 when the answer wasincorrect. The research data were processed with SPSS statistical software. The results showed a significant increasein the average knowledge of respondents from 5.11 2.059 at pre-test to 9.14 1.453 (p 0.05). Based on thetreatment and effectiveness test/gain scores, the average gain score was 69.9%. This study concludes that dental andoral health education through online media is positively effective for youth.KEYWORDS: Dental and Oral Health, Educational process, Online